Athlete presentations and injury frequency by sport at a sports medicine university clinic - Tahirbegolli, B.; Dincer, S.; Gözübüyük. Ö. B.; Degirmenci, U.; Yildiz, S.; Vehid, S. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: We aimed to investigate the profile of athletes by determining the branch of sports, type, and area of sustained sports injury, and the frequencies through athletes` presentations to the largest university clinic in one of the most crowded and athlete-populated cities of Turkey, Istanbul. METHODS: The study population comprised 1302 athletes who presented to the sports medicine clinic between the dates of July 1st, 2014, and June 30th, 2015. This record-based study examined all athlete presentations using the physical examination cards. RESULTS: Eight hundred and sixty-five of the athletes were male. The median age of applicants was 21 years (interquartile range 16-30 years), the median body mass index was 22.23 kg/m2 (range, 20.01-24.67 kg/m2), and the median years of sports activity was 5 years (range, 0-10 years). Presentations to the clinic were significantly higher in April (p=0.003). The most commonly injured body part was the knee and soccer was the leading sport among the patients; anterior cruciate ligament injury was the most common pathology among soccer players. CONCLUSIONS: Athletes who presented to our clinic most commonly sustained a lower extremity injury. It was notable that ligament injuries were seen as commonly as muscle injuries.